Efficacy of acupuncture for hypertension in the elderly: a systematic review and meta-analysis - Wang, Tianyi; Li, Hangyu; Feng, Shixing; Wang, Junqi; Qin, Wanli; Zhang, Yuan; Sun, Wen; Wang, Chenlu; Cai, Xuanyi; Han, Dongran; Liu, Jialin; Liu, Yixing (Frontiers in Cardiovascular Medicine, 2023)
Background: Hypertension has now developed into a major public health problem worldwide.Under the existing antihypertensive drug treatment paradigm, problems such as decreasing drug resistance and increasing drug side effects can occur for elderly patients. Acupuncture, a core technique in the non-pharmacological treatment of Chinese medicine, plays an important role in the treatment of elevated blood pressure.Objective: This study aimed to systematically evaluate the effect of acupuncture alone or in combination with antihypertensive drugs on the efficiency of reducing blood pressure and controlling blood pressure in elderly patients with hypertension.Methods: Articles of randomized controlled trials of acupuncture for hypertension in the elderly published before November 2022 were searched in 7 databases. The methodological quality of the literature was evaluated using the Cochrane Risk of Bias Assessment Tool. The primary outcome was the efficiency rate of blood pressure reduction, and the secondary outcome was the change in blood pressure after treatment. This is a provisional file, not the final typeset article. Results: This study conducted a systematic review and meta-analysis of 12 randomized controlled trials with a total of 1,466 subjects. Among the primary outcome -efficiency rate, acupuncture-only treatment and acupuncture combined with antihypertensive drug treatment were significantly different compared with drugs-only treatment. Among the secondary outcomes, SBP and DBP show no significant difference between acupuncture-only treatment and drug-only treatment. Compared to drugs-only treatment, acupuncture plus drugs has more significant efficiency in lowering SBP and DBP. For elderly patients with hypertension, acupuncture-only treatment has the same efficiency and antihypertensive effect compared to drug therapy and acupuncture plus drugs outperforms drugs-only treatment. If the patients receive therapy with less frequency per week and longer duration, there will be a more obvious antihypertensive effect. Due to the methodological defects in the included study and the limited sample size of this paper, more well-designed randomized controlled trials are needed for verification.